Struts & frets - Skovron, Jon (Amulet, 2009)
Sammy wants to be a musician, as was his grandfather, but while the band he is in is self-destructing, Sammy is too distracted by his grandfather's decline and confused feelings about his best friend to fix it--and his mother stays too busy to help.